The Williams and McCoy model of motivational spirited cognitive behavioral change communication - McCoy, Kathleen T.; Williams, Kimberly A. (Archives of psychiatric nursing, 2024)
The Williams and McCoy Motivational Spirited Cognitive Behavioral Change Communication (MIS-CBC) is an innovative model combining the spirit of motivational interviewing (MI) communication, and cognitive behavioral therapy (CBT) as a patient-centered care model to improve continuity of care while enabling patients to progress during therapy. Incorporating this model into Psychiatric Mental Health Advance Practice Nurse practice allows for provision of best practice with populations experiencing low motivation and subject to dropout. The model aims to improve patient motivation and engagement of CBT to achievement “full dose” CBT with more flexibility to significantly improve patient outcomes, particularly with patient populations subject to interruptions in psychotherapy. The Williams and McCoy MIS-CBC model has implications in areas of both practice and academia addressing episodic psychotherapy in populations where interruptions and dropout frequently occur.